การพัฒนาโครงข่ายทางจักรยานในเขตเทศบาลนครยะลา - ศรีสุดา วงษ์ชุ่ม (จุฬาลงกรณ์มหาวิทยาลัย, 2005)
The study of Bicycling Network Development in Yala Municipality is coherent with sustainable urban development policy by encouraging people to travel more by bicycles. According to the review on related plans, policies including theoretical concepts and research papers, it is found that a proposed bicycling network should be well integrated with existing modes of transportation, needs and present and future demands in bicycling use, standard design guidelines, physical, economic and social characteristics of the area, including its administrators’ specific views and plans. As Yala Municipality area is flat with a road network pattern in a mix-form of grid and radial patterns, people then have a variety of travel route choices which is rather suitable for bicycling network development. According to the field survey, the origin of travels is from the densely built-up residential area around Pipit Pakdee, Phang Mueng 4 and Siroros Roads, Its majority is short distance for the purposed of shopping and exercise. The popular transport vehicle is motorcycle, especially found to be preferable among students and low-income people. The study proposes two options of bicycling route network which are all compliant to the aforementioned requirements. Both options are then analyzed in terms of their spatial integration with the overall urban network using Space Syntax technique. The statistical result supports the option that presents the network developed along sub and minor roads, aimed to avoid heavity traffic and main roads in the area for the benefit of creating as safe bicycle travelling environment, rather than the one mostly developed along major roads. The better integrated option also statistically presents a more intelligible bicycling network for people. It is thus clear that the result confirms that the efficiency of bicycling network to reach destinations depends upon its spatial integration with surrounding urban network. The study also proposes preliminary recommendations in bicycling network planning within three phases along with a draft action plan to support the use of bicycle in the area such as; a promotion, a proposed construction of bicycle parking and other facilities, travel evaluation including other related transport and urban policies.